2018
DOI: 10.1111/odi.12795
|View full text |Cite
|
Sign up to set email alerts
|

Oral stomatitis and mTOR inhibitors: A review of current evidence in 20,915 patients

Abstract: Analysis of the reports with patients treated with everolimus, temsirolimus, and ridaforolimus showed a clear prevalence of stomatitis grade 1 or 2. These data differ from that of patients treated with conventional chemotherapy in which mucositis is predominantly of grade 3 or 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 152 publications
1
12
0
2
Order By: Relevance
“…Unlike results obtained from reviews about mucositis caused by conventional chemotherapy, in which mucositis is often severe and the most debilitating effect for patients,18 our analysis showed that the incidence of stomatitis of grade 1 or 2 is higher than that of grade 3 or 4. These results are consistent with our previous work 19. However, it must be taken into account that it is not possible to say if side effects are entirely due to everolimus therapy or combination with other drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike results obtained from reviews about mucositis caused by conventional chemotherapy, in which mucositis is often severe and the most debilitating effect for patients,18 our analysis showed that the incidence of stomatitis of grade 1 or 2 is higher than that of grade 3 or 4. These results are consistent with our previous work 19. However, it must be taken into account that it is not possible to say if side effects are entirely due to everolimus therapy or combination with other drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, other classes of targeted anti-cancer therapies with immunologic activities as mTOR inhibitors are known to induce stomatitis. In a review, Lo Muzio et al showed that the incidence rate of stomatitis based on the agent used was 54.76% for ridaforolimus, 27.02% for temsirolimus, and 25.07% for everolimus even if the onset of severe stomatitis (G3-G4) was uncommon [114]. Concerning a way to improve the adherence (acceptability) of patients to the chemopreventive protocol treatment, a recent study by Samimi et al indicated that patients could be more receptive to locally delivered chemopreventive compounds if they believe these substances useful for the treatment of cancer [115].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study, Krueger also reported that 40% of children developed stomatitis during mTOR inhibitor treatment [31]. According to the reviews by Martins [32] and Lo Muzio [33], grade 1 and grade 2 stomatitis occur more frequently in the first treatment cycle and seem to depend on the dose. Theoretically, mTOR inhibitors may induce an inflammatory reaction by inducing the release of keratinocyte cytokines, directly causing epithelial injury, which results in stomatitis [34].…”
Section: Discussionmentioning
confidence: 99%